Pesan Dakwah dalam Pementasan Wayang Kulit Lakon “Ma’rifat Dewa Ruci” Oleh Dalang Ki Enthus Susmono - Cecep Whinarno; Bustanul Arifin (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
On 7 November 2003 UNESCO has determined that Wayang Kulit is a world cultural heritage originating in Indonesia. State Minister of Culture and Tourism I Gede Ardika revealed, since November 7, 2003 the United Nations Educational, Scientific and Cultural Organization (UNESCO) has recognized wayang as the World Master Piece of Oral and Intangible Heritage of Humanity. Wayang is one of the pinnacles of Indonesia's cultural arts that is most prominent among many other cultural arts. Since the time of Wali Songo Wayang, it has been used as a means of communication and media for Islamic Da'wah initiated by Sunan Kalijaga. This research was conducted by analyzing the video of wayang Ma'rifat Dewa Ruci puppet performance by Ki Enthus Susmono using a qualitative approach, which is a research procedure that produces descriptive data in the form of words or writings from the observed data sources and by using Roland Barthes Semiotic analysis method.